Effect of therapeutic ultrasound on calcific supraspinatus tendinitis - Rahman, MH; Khan, SZ; Ramiz, MS (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2007 Jan;16(1):33-5. The abstract of this article is available on the PubMed website